Prediction of esophagogastric varices associated with oxaliplatin administration. Issue 11 (2nd November 2021) - Satta, Yosuke; Shigefuku, Ryuta; Watanabe, Tsunamasa; Mizukami, Takuro; Tsuda, Takashi; Suzuki, Tatsuya; Ehira, Takuya; Hattori, Nobuhiro; Kiyokawa, Hirofumi; Nakahara, Kazunari; Ikeda, Hiroki; Matsunaga, Kotaro; et al.
Abstract: Background: Oxaliplatin is a key drug for the chemotherapy of colorectal cancer; however, it is also known to cause non‐cirrhotic portal hypertension. We aimed to identify the characteristics of patients who developed esophagogastric varices (EGVs) after treatment with oxaliplatin. Methods: This study retrospectively analyzed patients with colorectal cancer who were treated with chemotherapy including oxaliplatin between 2010 and 2016. All patients were evaluated by contrast‐enhanced computed tomography (CE‐CT) every 3 months both during and after treatment; and endoscopy was performed when appearance of portal hypertension was suspected. Results: A total of 106 patients were divided into two groups: EGV formation ( n  = 6) and EGV non‐formation ( n  = 100). In the EGV group, platelet counts decreased and the size of the spleen calculated by CT (CT spleen index; CT‐SI) increased markedly. The highest area under the receiver operating characteristic curve (AUC) for the change in platelet counts was 0.81 (80% sensitivity and 83% specificity) at 3 months post treatment, and the maximum AUC for CT‐SI was 0.89 (79% sensitivity and 83% specificity) at 6 months post treatment. Conclusions: EGV formation could be predicted by the assessment of platelet counts and spleen size. If progressive splenomegaly and thrombocytopenia are observed not only during but also after completion of the oxaliplatin‐containing chemotherapy, EGVs should be confirmed by endoscopy for avoiding subsequent rupture. Abstract : We aimed to identify the characteristics of patients who developed esophagogastric varices (EGV) after treatment with oxaliplatin. If progressive splenomegaly and thrombocytopenia are observed not only during but also after completion of the oxaliplatin‐containing chemotherapy, EGV should be confirmed by endoscopy for avoiding subsequent rupture.